THE EFFECT OF GALLERY WALK AND MOTIVATION TOWARD STUDENTSâ READING COMPREHENSION OF NARRATIVE TEXT AT THE EIGHTH GRADE OF SMP N 1 PADANGSIDIMPUAN - yana, Aprida irma (JURNAL EDUCATION AND DEVELOPMENT, 2018)
In learning reading, teaching strategy and motivation have effect on the studentsâ reading comprehension. Gallery walk was used as the variation from reading learning strategies. The goal of this research is to find out the effect of gallery walk and motivation toward studentsâ reading comprehension of narrative text (fable). This research was classified into quasi experimental research. The population of this research was the Eighth grade students of SMPN 1 Padangsidimpuan. The technique that was used in selecting the sample was cluster random sampling. The sample of this research was VIII A as the experimental class and VIII C as the control class. The instruments which used in this research were reading comprehension test and questionnaire. The hypotheses were analyzed by using t-test and Two Ways ANOVA.  The finding shows that (1) Gallery walk strategy gives better effect on students reading comprehension compared to small group discussion. (2) Studentsâ with high motivation and taught by using gallery walk strategy have better reading comprehension compared to small group discussion. (3) Studentsâ with low motivation and taught by using gallery walk does not have better reading comprehension compared to small group discussion. (4) There is no interaction between motivation and studentsâ reading comprehension.